2013
DOI: 10.7314/apjcp.2013.14.5.2711
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1, Retinoblastoma and p16 Protein Expression in Carcinoma of the Gallbladder

Abstract: Background: Cancer of the gallbladder is a relatively rare neoplasm with a poor prognosis. The exact mechanisms of its genesis are not known and very little information is available on molecular events leading to labeling this as an orphan cancer. Materials and Methods: In this prospective case control study we evaluated the expression of p16, pRb and cyclin D1 by immunohistochemistry to study the G1-S cell-cycle check point and its possible role in gallbladder carcinogenesis. A total of 25 patients with gallb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Overexpression of cyclin D1 has been observed in 64% of patients in our study, however, previously published studies reported 5.6-41% overexpression and associated with low-grade tumors, papillary tumor morphology and predictors of survival. [2829424344] We also observed that overexpression was more in the patients with poorly differentiated tumors (84.6%), and distant metastasis (71.4%), although the result was not statically significant. This could be due to the fact that cyclin D1 influences the cell cycle by excreting its effect on cyclin dependent kinases.…”
Section: Discussionmentioning
confidence: 66%
“…Overexpression of cyclin D1 has been observed in 64% of patients in our study, however, previously published studies reported 5.6-41% overexpression and associated with low-grade tumors, papillary tumor morphology and predictors of survival. [2829424344] We also observed that overexpression was more in the patients with poorly differentiated tumors (84.6%), and distant metastasis (71.4%), although the result was not statically significant. This could be due to the fact that cyclin D1 influences the cell cycle by excreting its effect on cyclin dependent kinases.…”
Section: Discussionmentioning
confidence: 66%
“…Our tests on the cell cycle after regulating GRP78 expression reached the same conclusion, suggesting that GRP78 might affect the proliferation of PDAC cells by changing the cell cycle. Overexpression of CyclinD1 and CDK4/CDK6 was also observed in many human malignancies, including gall bladder cancer, endometrial carcinoma, and ovarian serous carcinomas 25 26 27 28 . Moreover, the apoptosis assay was also performed by FCS, but no significant difference was observed, likely because the spontaneous apoptosis of PDAC cell lines occurred at a relatively low level ( supplementary material ).…”
Section: Discussionmentioning
confidence: 99%
“…In this process, as an important member of the cyclin-dependent kinase inhibitors (CKIs), the p16 protein can competitively bind to CDK4/6, inhibit CDK4/6 activity, antagonize CCND1 function, and inhibit the progression of the cell cycle. However, the p16 gene is inactivated in most tumor tissues [5]. Our preliminary study demonstrated that the reactivation of p16 expression can induce the cell cycle arrest, promote the apoptosis of cancer cells, and inhibit the growth of tumors [6].…”
Section: Introductionmentioning
confidence: 97%